Digital Literacy: Thinking Critically About Language Skills in the Digital Age - Gushmanida, Gugun; Mustadi, Ali; Nugroho, Ikhlasul Ardi; Kusumo, Galih; Mapandi, Rohanie D (CV Sinergi Ilmu dan Publikasi, 2025)
The purpose of this study is to analyze students' critical thinking well by utilizing digital literacy. The method in this study is a qualitative method. Samples were taken from 2nd semester class A students at Sanata Dharma University, Yogyakarta. Data collection used a testing method. Critical thinking test questions function as instruments. Data analysis is the Miles & Huberman model analysis, namely qualitative data analysis, data reduction, data presentation and drawing conclusions. Based on the research data, it can be concluded that the level of critical thinking of students is very high related to four indicators, namely interpretation, analysis, explanation and self-regulation. The conclusion and explanation indicators are included in the moderate category. This is based on the table described for the level of critical thinking of students. There are several things that an institution or university must do to maintain these capabilities in the digital era, so that students can use them wisely and benefit many audiences, such as: providing outreach regarding the proper use of social media and providing tips for avoiding hoax news, providing Montessori training to develop critical thinking skills, providing Mendeley training using qualified references.